Comparative Study on Asymmetric Structure with Different Infill Materials Using ETABS - Sunitha G; Dr Lakshmi P S (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The study investigates the seismic behavior of irregular reinforced concrete (RC) frame structures with various infill materials using Response Spectrum Analysis (RSA). Infill walls, commonly made of brick or AAC blocks, are non-structural elements that influence the lateral stiffness and seismic response of buildings. The primary objective is to evaluate the effect of different infill materials on the lateral stability, displacement, drift, shear, and stiffness of an L-shaped asymmetric RC frame structure in a high seismic zone (Zone V), modeled using ETABS software. The analysis considers bare frames as well as frames with unreinforced masonry infills using two types of materials: brick and AAC blocks.The study demonstrates that the inclusion of infill materials significantly enhances the overall stiffness and base shear of the structure. Specifically, the brick infill models exhibited higher lateral resistance and lower displacement compared to the bare frame and AAC block models. However, the AAC block infill, with its lower weight and stiffness, showed increased displacements and reduced stiffness, particularly in the top stories of the asymmetric building. The results suggest that while masonry infill contributes to the structure's seismic resistance, material selection and the building’s plan irregularities play crucial roles in determining the seismic performance.
Keywords: Seismic analysis; RC frame; infill materials; Response Spectrum Analysis; ETABS; asymmetric structure; masonry infill; brick; AAC block; lateral displacement; story drift; seismic performance; base shear; stiffness; plan irregularity; earthquake resistance